The Limits of Monopolization Through Acquisition - Kamien, Morton I.; Zang, Israel (Quarterly Journal of Economics, 1990)
We address the question of whether competitive acquisition of firms by their rivals can result in complete or partial monopolization of a homogeneous product industry. This question is modeled in terms of two distinct three-stage noncoopera-tive games. Analysis of subgame perfect pure strategy Nash equilibria of these games discloses that, under simplifying assumptions, monopolization of an industry through acquisition is limited to industries with relatively few firms. Partial monopolization is either limited in scope or can be completely eliminated by prohibiting any owner from acquiring over 50 percent of the firms in the industry.